ANALISIS VARIASI GENETIK Saccharomyces cerevisiae Dl TAHAN ETANOL DENGAN RAPD (RANDOM AMPLIFIED POLYMORPHIC DNA) - Heddy Julistiono; Titin Yulineri; Sukamto Hanjono (Research Center for Biology-Indonesian Institute of Sciences, 1999)
Genetic variations among 3 cultures, which were treated with or without Mn of Saccharomvces cerevisiae D1, were analyzed using RAPD (Random Amplified Polymorphic DNA ) technique. The Mn-treatment of three cultures were as follows: the culture KMn was D1 strain, the culture Mn+ was D1 strain colony survived in ethanol 20%, which was previously treated with 0,5 mU MnSOt and the culture Mn- was a D1 colony survived in ethanol 20% without MnSOi treatment. Polymorphism of total DNA of the three cultures may indicate that mutation may occur in cells which were tolerant to ethanol. The locus or base change was not identified. However, since the oxygen uptake rate of the three cultures at catabolite derepression state were identical,the results suggest that the locus may not be in mitochondrial DNA encoding respiratory chain proteins. The relation between DNA polimorphic and ethanol tolerant cell is still to be clarified.